Towards a framework for assessing the impact of organisational capacity on integrated transport planning in district municipalities - Malila, Bonile Lucas (Department of Civil Engineering, 2018)
Some South African municipalities are facing challenges in performing transport planning functions. These challenges include a lack of organisational structure and human resource capacity, onerous planning frameworks, lack of guidance in preparing transport plans and lack of funding. To address these challenges, the Department of Transport has made various interventions, including the placement of interns in several municipalities across the country, reviewing transport planning frameworks and developing planning guidelines for the preparation of Integrated Transport Plans (ITPs). However, the impact on the ground has been minimal in terms of the quality of ITPs produced and their implementation. The impact of a lack of human resources and organisational capacity has not been investigated within a district municipal context. There is, therefore, a need to investigate capacity limitations and possible interventions as these factors may improve the quality and implementation of district municipality ITPs. The research reported upon in this dissertation was motivated by this need. Drawing on two case studies (the Alfred Nzo and Sedibeng District Municipalities), the study set out to assess how adequately District Municipalities (DMs) meet the minimum requirements for the preparation of ITPs. The study also set out to assess organisational capacity constraints that impact upon the performance of the two DMs surveyed. In fulfilling the aims of the study it was considered beneficial to use a mixed method qualitative survey and case study research approach, taking into account the research questions and limitations. A content analysis approach was adopted, whereby both the contents of the DITP documents, and the minimum requirements, were systematically examined. This ensured that the conclusions drawn from analysing the data collected were grounded. An assessment of the quality of the District Integrated Transport Plan (DITP), and the implementation thereof, also gave an indication as to whether the staff capacity employed by the DM was sufficient to fulfil its mandate. The study revealed that reviewing the minimum requirements might work to ensure that poorly resourced DMs are not subjected to requirements that are geared towards more affluent DMs. Learning from other countries, the study showed that having a monitoring chapter in the minimum requirements, and subsequently in the DITP, could ensure that quality control measures, as well as tools to monitor projects listed in the DITP, are put in place. The research showed that the Sedibeng DITP had an organisational structure and human resource capacity responsible for transport planning. It further revealed that the detailed nature of the Sedibeng DITP could be attributed to the fact that there is a relatively well-established organisational structure and a human resource capacity responsible for transport in the DM. Whilst on the case of Alfred Nzo DITP the research showed that there is no organisational structure and human resource capacity responsible for transport, which might account for the lack of details in its DITP. Furthermore, the research supported a hypothesis that the lack of human resources and organisational capacity have negative impact on the development and implementation of the ITPs at DMs level. In conclusion, the study recommends that transport planners should be employed by the National or provincial department of transport and be placed in DMs with the aim of increasing capacity whilst the DM is working on the reconfiguration of its organisational structure. Furthermore, the study recommends that the minimum content of the DITPs should be amended to meet the available capacity constraints and to align the categorisation of municipalities with that provided in the Municipal Structures Act. The minimum requirements should acknowledge this categorisation of municipalities, and where there is a need for the DM to scale down the minimum content of its plan based on capacity limitations or class of the DM, the minimum requirements should permit these deviations.